Behavioral Finance in the Digital Age: How Social Media Influences Investment Decisions - Idah Yuniasih; Nurul Aisyah; Rani Suryani (Pusat Riset dan Inovasi Nasional, 2025)
Retail investors today are heavily influenced by platforms like Reddit, TikTok, Twitter, and YouTube, where financial decisions are increasingly shaped by viral memes, influencer opinions, and emotionally charged content rather than company fundamentals or analytical research. Events such as the GameStop short squeeze and cryptocurrency pump-and-dump schemes illustrate how online communities can coordinate mass trading behavior, often driven by hype and group sentiment. This study examines how social media fuels behavioral biases like overconfidence, confirmation bias, and herding, while also enabling emotional contagion during market uncertainty—seen clearly during the COVID-19 crash. It explores how sentiment analysis models attempt to predict market movements using language data from posts and tweets, yet often fail to distinguish between authentic sentiment and manipulated signals generated by bots or coordinated campaigns. Influencers without financial credentials regularly offer investment “tips” that go viral, drawing millions of views but little regulatory oversight. These patterns show that behavioral finance must evolve to account for real-time, crowd-based, platform-driven investor behavior. Future work should compare platform-specific features—such as Reddit’s upvote dynamics vs. TikTok’s algorithmic exposure—and assess how misinformation, social validation, and low financial literacy combine to distort market behavior at scale.